The Effectiveness of Progressive Pruning on Looses Production - Nugraha, Bima Sakti Novi Tri; Wirianata, Herry; Budihardjo, Kadarwati (Tropical Plantation Journal, 2025)
Oil palm canopy is formed every month as many as 1-3 fruits, depending on the age and growth of the plant. Each oil palm canopy supports the formation of leaf/frond positions that are arranged in a spiral. Progressive pruning of the main shoots is carried out directly by harvest workers (not the Special Main Shoot Work Team) and is carried out simultaneously when cutting the fruit while still referring to the basic principle of the number of productive fronds that must still be maintained according to the provisions (leaf area index). This study aims to determine the role of the progressive pruning system in minimizing looses (bunches and looses fruit) in oil palm plantations. The basic method used in this study is a quantitative descriptive method using t-test analysis, the parameters used are the looses of bunches and looses fruit. The conclusion of the study is that the progressive pruning system can reduce losses of oil palm fruit (bunches) and loose fruit, compared to the periodic pruning system at the overall looses point of the three looses point chains, namely at the main, plate and market.